Treatment of root‐fractured maxillary incisor with Thermafil obturator - (:unkn) unknown (My University, 1993)
Abstract This case report describes the treatment of a maxillary left central incisor with intra‐alveolar horizontal root fracture in the middle of the root. The pulp of the coronal segment was necrotic and endodontic treatment was performed. Instrumentation of the root canal through the fracture line was carried out and the tooth was obturated with Thermafil in order to bring about a union of the fragments. At the 24‐month follow up examination the tooth was functionally and esthetically normal. Radiographically no pathosis was evident in the periapical or fracture areas. Copyright © 1993, Wiley Blackwell. All rights reserved
Keywords: endodontic treatment; pulp necrosis; root fracture; Thermafil